Bologna – Redemption wax, Redemption flesh Wax modeling for the studying and teaching of Anatomy at the University of Bologna - Leonardi, Luisa; Bettini, Giuliano; Corrain, Lucia; Mancini, Cristian; Ruggeri, Alessandra; Sarti, Carlo (Italian Journal of Anatomy and Embryology, 2018)
The video depict a historical reconstruction of the birth and development of anatomical ceroplas- tics work in the “felsinea” city. The first anatomical wax modelings were prepared in 1742, in the scientific laboratories by Ercole Lelli (1702-1766), Giovanni Manzolini (1700-1750) and Anna Morandi (1714-1774). By the end of the eighteenth century, the affirmation of the anatomo-pathological para- digm gave to the study of “diseases” a comparative twist: new diagnosis began to relay on expe- rience acquired during investigations of similar cases made in the past. To achieve this goal, they recorded experiences not only through written words, but also through anatomic modelings. The ductility of the waxes was instrumental to reproduce the various aspects of an illness bridged the gap between life and death since the replication of the visible consequences of an illness made when the patient was still alive allowed scientists to observe and study the damage inflicted by the disease also after the patient had been long dead. This transition from medicine to the art applies also to animal disease, which progressively acquires its own autonomy and is given birth to a very large waxes col- lection made by leading ceroplasts Giuseppe Astorri (1785-1852) and Cesare Bettini (1814-1885) who produced wax reproductions of normal and pathological human anatomy and pathological veterinary anatomy. The large collection of wax models is retained in Museum of “Palazzo Poggi”, in Museum of Anatomical Waxes “Luigi Cattaneo” and in the Museum of Veterinary Pathology “Alessandrini Ercolani”, all togheter part of the University Museum System (SMA).